Cellular localization and regional distribution of an angiotensin II-forming chymase in the heart. - Urata, H (1993)
The human heart is a target organ for the octapeptide hormone, angiotensin II (Ang II). Recent studies suggest that the human heart contains a dual pathway of Ang II formation in which the major Ang II-forming enzymes are angiotensin I-converting enzyme (ACE) and chymase. Human heart chymase has recently been purified and its cDNA and gene cloned. This cardiac serine proteinase is the most efficient and specific Ang II-forming enzyme described. To obtain insights into the cardiac sites of chymase-dependent Ang II formation, we examined the cellular localization and regional distribution of chymase in the human heart. Electron microscope immunocytochemistry using an anti-human chymase antibody showed the presence of chymase-like immunoreactivity in the cardiac interstitium and in cytosolic granules of mast cells, endothelial cells, and some mesenchymal interstitial cells. In the cardiac interstitium, chymase-like immunoreactivity is associated with the extracellular matrix. In situ hybridization studies further indicated that chymase mRNA is expressed in endothelial cells and in interstitial cells, including mast cells. Tissue chymase levels were determined by activity assays and by Western blot analyses. Chymase levels were approximately twofold higher in ventricles than in atria. There were no significant differences in chymase levels in ventricular tissues obtained from non-failing donor hearts, failing ischemic hearts, or hearts from patients with ischemic cardiomyopathy. These findings suggest that a major site of chymase-dependent Ang II formation in the heart is the interstitium and that cardiac mast cells, mesenchymal interstitial cells, and endothelial cells are the cellular sites of synthesis and storage of chymase. In the human heart, because ACE levels are highest in the atria and chymase levels are highest in ventricles, it is likely that the relative contribution of ACE and chymase to cardiac Ang II formation varies with the cardiac chamber. Such differences may lead to differential suppression of cardiac Ang II levels during chronic ACE inhibitor therapy in patients with congestive heart failure.